CIRCULAR ECONOMY AND TRADE: THE CHANGING PARADIGM FOR COMMERCIAL EXCHANGES BETWEEN COUNTRIES - Formenti, Lorenzo; Gregol, Tamara; Pacini, Henrique (REVISTA PARADIGMA, 2019)
With the proper alignment of enablers in various markets, as well as shifting consumer preferences, a circular economy can be an important contributor to goals set in the Paris Agreement and the SDGs. Its potential cannot be realised without the facilitation of international trade. As a global economy, we need to move from a mercantilist model of resource trade – where some nations accumulate materials which are costly to reprocess in their territories – to a model in which resources flow back to regions which comparative advantages for their recycling. Negotiating agreeable conditions for all countries to do so it essential to make circular economy the core of our growth strategies.